2015
DOI: 10.1111/risa.12410
|View full text |Cite
|
Sign up to set email alerts
|

“The Dose Makes the Poison”: Informing Consumers About the Scientific Risk Assessment of Food Additives

Abstract: Intensive risk assessment is required before the approval of food additives. During this process, based on the toxicological principle of "the dose makes the poison,ˮ maximum usage doses are assessed. However, most consumers are not aware of these efforts to ensure the safety of food additives and are therefore sceptical, even though food additives bring certain benefits to consumers. This study investigated the effect of a short video, which explains the scientific risk assessment and regulation of food addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…A number of prevalent misconceptions among laypeople regarding both natural and synthetic chemicals were identified, including dose–response insensitivity and the underestimation of the toxicity of chemicals of natural origin. The insensitivity to dose–response relationships and exposure scenarios was also identified in previous research (Bearth et al., ; Dickson‐Spillmann et al., ; Kraus et al., ; Slovic et al., ). Rather than a dose–response function, laypeople tend to perceive a causal relationship between exposure to a chemical and inevitable consequences, especially in the case of chemicals associated with carcinogenicity (MacGregor, Slovic, & Malmfors, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A number of prevalent misconceptions among laypeople regarding both natural and synthetic chemicals were identified, including dose–response insensitivity and the underestimation of the toxicity of chemicals of natural origin. The insensitivity to dose–response relationships and exposure scenarios was also identified in previous research (Bearth et al., ; Dickson‐Spillmann et al., ; Kraus et al., ; Slovic et al., ). Rather than a dose–response function, laypeople tend to perceive a causal relationship between exposure to a chemical and inevitable consequences, especially in the case of chemicals associated with carcinogenicity (MacGregor, Slovic, & Malmfors, ).…”
Section: Discussionsupporting
confidence: 71%
“…In fact, a greater understanding of the risk assessment process is associated with a lower risk perception of chemicals, particularly in the case of synthetic chemicals (Dickson‐Spillmann et al., ; Kraus et al., ; Shim et al., ). Consequently, consumers probably require a basic knowledge of chemical and toxicology principles to enable them to make fact‐based decisions regarding chemical‐containing products (Bearth, Cousin, & Siegrist, ; Dickson‐Spillmann et al., ; Dickson‐Spillmann, Siegrist, Keller, & Wormuth, ; Kraus et al., ; Shim et al., ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A large body of evidence from other areas of research suggested that the imbalance in knowledge between experts or stakeholders and consumers might lead to different conclusions regarding risk perception, benefit perception, acceptance and behaviour . For some potentially beneficial innovations, knowledge provision had proved successful to reduce risk perception and improve acceptability . However, innovative technologies and applications are not necessarily judged by weighing the risks and benefits and considering objective facts by either experts or lay‐people .…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] For some potentially beneficial innovations, knowledge provision had proved successful to reduce risk perception and improve acceptability. 35,36 However, innovative technologies and applications are not necessarily judged by weighing the risks and benefits and considering objective facts by either experts or lay-people. 37 Frequently, risk judgements and decisions are influenced by previous experiences, effects or other readily available factors to reduce cognitive load.…”
mentioning
confidence: 99%
“…An experimental group was shown a short video about results of a scientific assessment that focused on health risks related to food safety (natural and artificial food additives). After having seen the video, consumers from the experimental group had authentically better awareness, more positive attitudes towards food products and lower anxiety than consumers from the reference group [25].…”
mentioning
confidence: 96%